Efektifitas Dan Kontribusi Pbb-P2 Terhadap Pendapatan Asli Daerah Kabupaten Purworejo Tahun 2018-2022 (Progress, 2025)
The purpose of this study is to determine the level of effectiveness and contribution of Rural and Urban Land and Building Tax (PBB-P2) to the Original Regional Income of Purworejo Regency in 2018-2022. The stages in analyzing the level of effectiveness are carried out by comparing the target revenue and the realization of PBB-P2 revenue. Contribution analysis can be carried out by comparing the realization of PBB-P2 revenue and the realization of Original Regional Income owned by Purworejo Regency. The data analysis technique used is quantitative descriptive. Quantitative descriptive analysis is used to explain and present data obtained from agencies by providing a general description in accordance with the reality at the time of conducting research analyzing the level of effectiveness of Rural and Urban Land and Building Tax (PBB-P2). Based on the research conducted by the author, the results of the study were obtained, namely the level of effectiveness of Rural and Urban Land and Building Tax (PBB-P2) revenues in Purworejo Regency in 2018-2022 averaged 109.712% and showed very effective criteria, the level of contribution of Rural and Urban Land and Building Tax (PBB-P2) revenues to Purworejo Regency's Original Regional Income in 2018-2022 averaged 9.46% and fell into the very poor criteria.